Sisyrinchium arguellesiae (Iridaceae, Sisyrinchieae) a new species from the state of Querétaro - Ceja Romero, Jacqueline; Espejo Serna, Adolfo; Lopez-Ferrari, Ana Rosa (Instituto de Ecología, A.C., 1998)
Sisyrinchium arguellesiae, a new species from Querétaro, México is described and illustrated. The new species is recognized by its flowers lasting two days and by its tepals with a white-translucent spot in the base that in the perianth looks like a central "eye".